Study like a champ : the psychology-based guide to "grade A" study habits - Gurung, Regan A. R.; Dunlosky, John (APA LifeTools., 2023)
This engaging, student-friendly book debunks major myths about studying and provides practical tips for how students can learn to study smarter, not harder. Cognitive science has revealed the hidden secrets of what really works for studying. Written by psychologists who are experts in the science of study habits, Study Like a Champ outlines clear steps students can use throughout their high school and college careers to plan, monitor, and evaluate their learning. Numerous examples and self-assessments will help students of all ages apply these strategies to their own unique situations to help them create and maintain habits that foster life-long learning. Psychologists Regan A.R. Gurung and John Dunlosky are award-winning teachers and researchers who have spent years conducting studies on how students learn. Not only have they published a significant number of scientific peer-reviewed papers on the topic, but they have received national recognition as teachers.